Hepatitis B virus surface protein induces sperm dysfunction through the activation of a Bcl2/Bax signaling cascade triggering AIF/Endo G–mediated apoptosis. (1st February 2021) - Han, Ting‐Ting; Huang, Ji‐Hua; Gu, Jiang; Xie, Qing‐Dong; Zhong, Ying; Huang, Tian‐Hua
Abstract: Background: Hepatitis B virus (HBV) was found to exist in semen and male germ cells of patients with chronic HBV infection. Our previous studies demonstrated that HBV surface protein (HBs) could induce sperm dysfunction by activating a calcium signaling cascade and triggering caspase‐dependent apoptosis. However, the relationship between sperm dysfunction caused by HBs and caspase‐independent apoptosis has not been investigated. Objectives: To evaluate the effects of HBs exposure on sperm dysfunction by activating caspase‐independent apoptosis. Materials and methods: Spermatozoa were exposed to HBs at concentrations of 0, 25, 50, and 100 μg/mL for 3 h. Flow cytometry, qRT‐PCR, immunofluorescence assay, ELISA, and zona‐free hamster oocyte penetration assays were performed. Results: With increasing concentrations of HBs, various parameters of the spermatozoa changed. The number of Bcl2‐positive cells declined and that of both Bax‐positive cells and Apaf‐1–positive cells increased. The transcription level of Bcl2 increased and that of both Bax and Apaf‐1 declined. The average levels of AIF and Endo G declined in mitochondria and increased in the cytoplasm and nucleus. The sperm DNA fragmentation index increased. The mean percentages of live spermatozoa declined and that of both injured and dead spermatozoa increased; and the sperm penetration rate declined. For the aforementioned parameters, the differences between the test and the control groups were statistically significant. Conclusion: HBs exposure can activate the Bax/Bcl2 signaling cascade that triggers AIF/Endo G–mediated apoptosis, resulting in sperm DNA fragmentation, sperm injury, and death, and a decrease in the sperm fertilizing capacity. This new knowledge will help to evaluate the negative impact of HBV on male fertility in HBV‐infected patients.